Eagle's syndrome—A non-perceived differential diagnosis of temporomandibular disorder. (2015) - Thoenissen, P.; Bittermann, G.; Schmelzeisen, R.; Oshima, T.; Fretwurst, T.
Highlights: We investigated Eagle's syndrome as a common origin of head and neck pain and differential diagnosis of temporomandibular joint disorders. Styloid syndrome is a cause of head and neck pain, resulting from the presence of an elongated styloid process above 25 mm as Eagle believed. Eagle's Syndrome can be diagnosed easily upon panoramic imaging and an analysis of reported symptoms in a routine check by a dentist. Using CT-navigation combined with endoscopy in an external surgical approach should be the treatment of choice when a patient is faced with long term pain of head and neck region. Abstract: Introduction: This article unveils a case of the classic styloid syndrome and states that panoramic imaging and ultrasound can be an alternative to computed tomography. In addition, the endoscope-assisted extraoral approach using CT-based navigation is useful. Eagle's Syndrome is an aggregate of symptoms described by Eagle in 1937. He described different forms: the classic styloid syndrome consisting of elongation of the styloid process which causes pain. Second, the stylo-carotid-artery syndrome which is responsible for transient ischemic attack or stroke. Presentation of case: Using the example of a 66 years old male patient suffering from long term pain, we explain our diagnostic and surgical approach. After dissecting the styloid process of the right side using an extraoral approach, the pain ceased and the patient could be discharged without any recurrence of the pain up to this point. Discussion: Eagle's syndrome, with its similar symptoms, is rather difficult to differentiate from temporomandibular joint disorders (TMD), but can be easily excluded from possible differential diagnoses of TMD using panoramic radiographs and ultrasound. Conclusion: Making use of low cost and easily accessible diagnostic workup techniques can reveal this particular cause for chronic pain restricting quality of life. Thereby differentiation from the TMD symptomatic complex is possible.